Use of Social Media in Schools and Madrasas: A Systematic Review of Social Studies Learning Innovations - Asy'arie, Bima Fandi; Mariyana, Weni; Haq, Fauzi Nadziiran; As’ad, Muhammad Syihab; Aditia, Dimas (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
This study aims to identify and analyze the benefits and negative impacts of using social media (TikTok, YouTube, WhatsApp) as an innovation in Social Science learning in schools and madrasas. This research used a systematic literature review (SLR) type, with a qualitative approach. Research period focused on years (2020-2024). Database was obtained from “Google Scholar” and “ScienceDirect”. Then, we conducted a bibliometric analysis to understand the bibliographic landscape with “VOSviever”. To obtain the credibility of the data as the main finding of 35 article documents, we used the “Publish or Perish”. The findings include: First, the use of social media in learning can create effective learning situations, provide quick access, allow for discussions between teachers and students online. With teacher guidance, social media can enrich the learning experience and increase student engagement in learning. Second, that the use of social media in learning might have negative effects such as internet connection disruptions that affect learning, indications of addiction to negative content, disruption of student’s concentration, reduced direct interaction, and problems such as privacy and security. The integration of digital platforms in learning can increase student motivation, expand access to information, and encourage collaboration. However, there is a need for teacher training on digital literacy to ensure wise use, and reduce the risk of spreading irrelevant information. This research encourages the curriculum development that accommodates the planned use of social media, so that students not only become consumers of information, but also creators of critical and creative content.